Under the radar: the widespread use of ‘Out of Court Resolutions’ in policing domestic violence and abuse in the United Kingdom - Westmarland, Nicole (The British journal of criminology, 2018)
The suitability of ‘out of court resolutions’ (restorative justice and community resolutions) in cases of domestic abuse is theoretically contentious and empirically under-researched. This study investigated the nature and extent of out of court resolutions for domestic abuse using the Freedom of Information Act. Out of court resolutions were used by every UK police force except Scotland to respond to over 5,000 domestic abuse incidents (including intimate partner abuse) in 2014. Some of these incidents related to offences with sentencing tariffs up to life imprisonment. Such widespread use has been taking place ‘under the radar’ in stark contrast to police guidance, has immediate implications for policy and practice, and fundamentally shifts the research terrain in this field.